Technological tools as didactic resource for various educational modalities - Meza, Werme Esaud Yenchong; Saltos, Elisa Rafaela Rodriguez; Loor, Brenda Michelle Vallejo; Solorzano, Maria Julieta Ponce (International research journal of management, IT and social sciences, 2020)
Technological tools have generated a breakthrough in all areas where humans are immersed; education is one of them, technology has created a new adaptation in the educational aspect to achieve the rhythm of other sciences to keep up with the technological world, teaching resources are of great help for the development of learning in the students since a new teaching methodology is generated for them and this will allow fruitful results to be obtained in the cognitive development of the same. There are several alternatives where great changes can be generated in the educational system, venturing into areas where the student can choose various technological alternatives for further development. The objective was to analyze the use of technological tools as a didactic resource for various educational modalities, it was carried out under the documentary methodology since the information was sought from different investigations on the various educational modalities that can be used through technological tools.